Lu'batu Bingo li Tarqiyati Itqâni al-Mufradât al-'Arabiyyah: Bahts Tajrîbî li Thalabati al-Madrasah al-Ibtidâiyyah bi Indûnîsiyâ - Fudhaili, Achmad (Alibbaa': Jurnal Pendidikan Bahasa Arab, 2023)
One of the most important aspects of language learning is vocabulary. Many students have difficulty mastering it. The researcher wants to reveal how effectively the Bingo game method increasesabic vocabulary mastery. This study uses a quantitative approach, with a pre-experimental design and a one-group pretest-posttest design. The population of this study was 20 grade V students at SDN Guluk-Guluk II Sumenep. The sampling method is the saturated sample method. Researchers collect information through pretest and posttest. For data analysis, the SPSS 22 application was used which included the Kolmogorov-Smirnov normality test. The researcher then used the SPSS 22 application to test the hypothesis with the non-parametric Mann-Whitney test. According to the findings of this study, bingo games can statistically improve vocabulary mastery by 79.6%. The results of the Mann-Whitney hypothesis test show this. The implication of the findings of this study is that bingo games can be used as an effective method for increasing vocabulary mastery in fifth-grade elementary school students. However, because this research was only conducted in class V SD, the results cannot be applied in general to all grade levels. Therefore, further research is needed to find out whether bingo games are also effective for use at other grade levels.